THE DIFFERENCES CATCHING BOTTOM GILLNET IN THE AFTERNOON AND NIGHT AT LUBUK PUDING VILLAGE OF BURU SUBDISTRICT OF KARIMUN DISTRICT OF KEPULAUAN RIAU PROVINCE - Zulkifli '; Bustari '; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on February 2016 in Lubuk Puding village of Buru Subdistrict of Karimun District of Kepulauan Riau Province. The purpose of this study was to determined differences drift gillnet catches according of day to the operational. This resech used a survey method.The night catches almost three time bigger then day light catches in respectively total catches is 332,1 kg (41 fish) and 127,7 kg (16 fish). The calculation of t test there are differences in the bottom gillnet catches the day light and at night. Keyword : Bottom gillnet, catches in afternoon and at night